The effect of Learning Strategy of Assurance, Relevance, Interest, Assessment, and Satisfaction (Puzzle Vs Video) on Ecosystem to Students Cognitive Learning Result - Marwanto, Rosid; Seribulan, Muhamad Nurdin Matondang; Isfaeni, Hanum (Universitas Negeri Jakarta, 2014)
Learning strategy is an important key for successful learning process. Inappropriate learning strategy causing student to get bored easily, more passive, and loss focus on the learning topic. ARIAS (Learning Strategy of Assurance, Relevance, Interest, Assessment, and Satisfaction) is a learning strategy encouraging student to learn biology in fun and interesting ways by which higher learning result may be achieved. This research was conducted in MAN 8 Jakarta on November 2012 using an experimental method with posttest-only group design. An overall sample of 60 grade 10 students was selected by simple random sampling. They were divided into experimental and control groups consisted of 30 students. Instruments used in this research classified as multiple-choice questions. Based on the result, Average students cognitive learning result in experimental group treated by puzzle and control class treated by video display showed 74.03 and 61.93, respectively. Prerequisite testing of Kolmogorov-Smirnov test and F-test showed a normal and homogenous data. The hypothesis testing conducted by t-test at confidence level of 95% showed that t value > t table at 1.91 > 1.67, which rejected the null hypothesis. Therefore, it can be concluded that application of ARIAS learning strategy with puzzle has better effect on students cognitive learning result than with video display.